Corrosion Behavior and Failure Mechanism of Prestressed Rock Bolts (Cables) in the Underground Coal Mine. (2nd March 2021) - Wang, Qiong; Wang, Fengnian; Ren, Aiwu; Peng, Rui; Li, Jian
Abstract : Premature failure of rock bolts (cables) due to stress corrosion cracking (SCC) is a phenomenon that has been reported to occur in the underground environment. In the 1990s, many failure accidents of bolts which occurred in the United Kingdom were caused by SCC [1]. In this study, the corrosion behavior and failure mechanism of rock bolt (cable) samples obtained from the underground coal mine were examined and discussed. Macroscopic observation and weight loss tests were carried out for the bolts' corrosion characteristics without failure. The results show that the bolts with short service time (1.5–2 yrs) underwent uniform corrosion. However, bolts with longer service time (3–8 yrs) experienced different pitting corrosion degrees. The corroding degree of different parts of bolt samples shows the following decreasing trend: bolt head > bolt end > free section. The absolute corrosion degree increased with the service time, while the corrosion rate was the highest in the early stage and dropped down in the later stage. At the same time, the macro- and micromethods were used to analyse the failure mechanism in the broken cable sample. Failure of one cable sample with a medium service life (6 yrs) was found to be controlled by the SCC. It was induced by long-term action of O, Cl, and S in the surrounding rock environment and resulted in pitting corrosion. The pitting corrosion reduced the outer diameter of the rock cable and its bearing capacity, leading to the final fracture.